2012
DOI: 10.1007/s10508-012-9939-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Fantasies and Viewing Times Across the Menstrual Cycle: A Diary Study

Abstract: Recent research has revealed that many aspects of female sexuality change across the menstrual cycle. In this study, we examined changes in sexual fantasies and visual sexual interests across the menstrual cycle. A total of 27 single, heterosexual women (M age=21.5 years) not using hormonal contraceptives answered questions on a web-based diary every day for 30 days about their sexual fantasies and behaviors. Twenty-two of them also completed a viewing time task during three different menstrual cycle phases (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…This is especially true given that women experience greater variability in hormone levels than do men, and women's sexuality appears to be sensitive to these fluctuations across the menstrual cycle [for a review, see 97] and to oral contraceptive use [for a review, see [98]. Prospective studies of naturally-cycling women's sexual desire, as measured by sexual fantasies and sexual thoughts recorded daily across entire menstrual cycles, show marked increases during ovulation [e.g., 46,47,99,100], suggesting a greater sensitivity to sexual cues at midcycle. Unfortunately, there are very few equivalent studies examining fluctuation in men's sensitivity to sexual incentives over time.…”
Section: Sexual Desire Across Timementioning
confidence: 99%
“…This is especially true given that women experience greater variability in hormone levels than do men, and women's sexuality appears to be sensitive to these fluctuations across the menstrual cycle [for a review, see 97] and to oral contraceptive use [for a review, see [98]. Prospective studies of naturally-cycling women's sexual desire, as measured by sexual fantasies and sexual thoughts recorded daily across entire menstrual cycles, show marked increases during ovulation [e.g., 46,47,99,100], suggesting a greater sensitivity to sexual cues at midcycle. Unfortunately, there are very few equivalent studies examining fluctuation in men's sensitivity to sexual incentives over time.…”
Section: Sexual Desire Across Timementioning
confidence: 99%
“…Bullivant et al, 2004 cf. Dawson, Suschinsky, & Lalumière, 2012). Some studies also indicate that menstrual phase during the initial exposure to sexual stimuli may have a stronger effect on women's sexual responses than the actual cycle phase at the time of testing but other studies do not (e.g., Suschinsky et al, 2014;Wallen & Rupp, 2010cf.…”
Section: Discussionmentioning
confidence: 99%
“…Baumeister [74] noted that there is greater flexibility among androphilic women's sexuality compared with men's. Studies consistently find significant variability in the gender of the sexual target reported in the sexual fantasies [75,76] and sexual experiences [63,77] of androphilic women, despite these women reporting predominant or exclusive sexual attractions to men. Together, these findings add credence to the idea that preferred and nonpreferred targets may hold incentive value for androphilic women; this, coupled with concomitant arousal, would result in activation of the motivational system, leading to nonspecific patterns of sexual desire.…”
Section: Discussionmentioning
confidence: 99%